Adult spinal cord ependymal layer: a promising pool of quiescent stem cells to treat spinal cord injury - Malas, Stavros; Panayiotou, Elena (Frontiers in Physiology, 2013)
Spinal cord injury is a major health burden and currently there is no effective medical intervention. Research performed over the last decade revealed that cells surrounding the central canal of the adult spinal cord and forming the ependymal layer acquire stem cell properties either in vitro or in response to injury. Following spinal cord injury activated ependymal cells generate progeny cells which migrate to the injury site but fail to produce the appropriate type of cells in sufficient number to limit the damage, rendering this physiological response mainly ineffective. Research is now focusing on the manipulation of ependymal cells to produce cells of the oligodendrocyte lineage which are primarily lost in such a situation leading to secondary neuronal degeneration. Thus, there is a need for a more focused approach to understand the molecular properties of adult ependymal cells in greater detail and develop effective strategies for guiding their response during spinal cord injury.